Catecholaminergic depletion within the prelimbic medial prefrontal cortex enhances latent inhibition - Nelson, Andrew J.D.; Thur, Karen E.; Marsden, C.A.; Cassaday, Helen J. (Elsevier, 2010)
Latent inhibition (LI) refers to the reduction in conditioning to a stimulus that has received repeated non-reinforced pre-exposure. Investigations into the neural substrates of LI have focused on the nucleus accumbens (NAc) and its inputs from the hippocampal formation and adjacent cortical areas. Previous work has suggested that lesions to the medial prefrontal cortex (mPFC), another major source of input to the NAc, do not disrupt LI. However, a failure to observe disrupted LI does not preclude the possibility that a particular brain region is involved in the expression of LI. Moreover, the mPFC is a heterogeneous structure and there has been no investigation of a possible role of different regions within the mPFC in regulating LI under conditions that prevent LI in controls. Here, we tested whether 6-hydroxydopamine (6-OHDA)-induced lesions of dopamine (DA) terminals within the prelimbic (PL) and infralimbic (IL) mPFC would lead to the emergence of LI under conditions that do produce LI in controls (weak pre-exposure). LI was measured in a thirst motivated conditioned emotional response procedure with 10 pre-exposures to a noise conditioned stimulus (CS) and two conditioning trials. Sham-operated and IL-lesioned animals did not show LI and conditioned to the pre-exposed CS at comparable levels to the non-pre-exposed controls. 6-OHDA lesions to the PL, however, produced potentiation of LI. These results provide the first demonstration that the PL mPFC is a component of the neural circuitry underpinning LI.